PARTIAL CHARACTERIZATION OF LIPASE FROM COCOA BEANS (Theobroma cacao. L.) OF CLONE PBC 159 - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2008)
ABSTRACT A study was caffied out to characterize the cocoa lipase from cocoa beans (Theobroma cacao, L.) of clone PBC 159. The optimum temperature of cocoa lipase was 30-40 .C and the pH optimum was 7.0-8.0. The moleculer weight of the lipase enzyme was in between 45-66 kOa. The results indicate that Kmvalue for cocoa bean lipase was 2.63 mM, when trimyristin was used as a substrate. The incubation of cocoa bean lipase with triolein and tributyrin (as substrate) yielded Kmof 11.24 and 35.71 mM, respectively. The Vmaxvalue obtained from the incubation of the lipase with a wide range of substrates, including tributyrin, trimyristin and triolein, are expressed as pmole acidlmin/mg protein for cocoa lipase. Vmax values decreased with the increase in the triacylglycerol chain-length, with Vmax values of 27.78, 13.16 and 11.63 pmole acidlmin/mg protein when incubated with tributyrin, trimyristin and triolein, respectively. Inhibition of lipase occurred in the presence of diisopropyl fIourophosphate, Nbromosuccinimide and 5,5-dithiobis-(-2-nitrobenzoic acid). Keywords: characterization, lipase, cocoa beans